Pengaruh Penerapan Model Quick On The Draw Terhadap Kemampuan Memahami Teks Biografi Siswa - Eunike Manurung (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the ability to understand biographical texts for class X students of SMK N 1 Lumban Julu in the 2022/2023 academic year. The method used in this study is an experimental method with a two group post-test design. The sample in this study were students of class X RPL 1 which consisted of 30 students and students of class X RPL 2 with a total of 30 students. The data analysis technique used in this study is quantitative data by using analysis requirements test, homogeneity test, and hypothesis testing. The results showed that the average score of the ability to understand biographical texts of the experimental class students was 84.2 belonging to the good category while the average value of the control class was 59.03 belonging to the sufficient category and did not meet the Minimum Completeness Criteria (KKM), namely 75. Based on the t test, it was obtained a significance level value of α = 0.05 with dk = N-1 = 29, so that a ttable value of 2.045 was obtained. Thus it is concluded that tcount > ttable, namely 8.446 > 2.045 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant effect of using the Quick On the Draw learning model on the ability to understand biographical texts for class X students of SMK N 1 Lumbanjulu in the 2022/2023 Academic Year.